Peningkatan Hasil Belajar Matematika Dengan Pendekatan Crt Pada Peserta Didik Kelas 1 SDN 2 Prambanan - Ferryka, Putri Zudhah; Suwartini, Sri; Susanti, Maria Melani Ika; Rofisian, Nela; Rahmawati, Isna; Irawati, Iisrohli (Universitas Muhammadiyah Magelang, 2025)
The purpose of this study was to determine the improvement in mathematics learning outcomes of grade 1 students of SD Negeri 2 Prambanan with the CRT approach. This study was motivated by the low learning outcomes of students, seen from the learning outcomes of students who were still below the KKTP as many as 73.5% of students. This is due to the lack of teacher innovation in implementing learning so that students find it difficult to understand the learning material. The type of research used was classroom action research with the Kemmis & Mc Taggart model. This research model consists of four stages, namely planning, implementing actions, observation, and reflection. The subjects of the study were all grade 1A students of SD N 2 Prambanan consisting of 28 students with details of 15 male students and 13 female students. Data collection techniques used observation sheets, measurement of learning test results, and documentation. The data analysis technique used was descriptive analysis with a percentage. The results in this study showed an increase in learning outcomes in each cycle. The learning outcomes of students who had completed cycle 1 were 19 students with a percentage of 67.8%. In cycle 2, there were 25 students who had completed it with a percentage of 89.2%. The results revealed a significant increase in student learning outcomes in mathematics on the material of recognizing geometric shapes through the CRT approach.